1999
DOI: 10.1007/bf02347196
|View full text |Cite
|
Sign up to set email alerts
|

T-for-H exchange reaction between HTO vapor and two functional groups in an aromatic compound in a gas-solid system

Abstract: The hydrogen-isotope exchange reaction (T-for-H exchange reaction) between HTO vapor and an aromatic compound having two different kinds of functional groups has been observed at several temperatures. The rate constant (k) for each functional group in the T-for-H exchange reaction was obtained by using both the A"-MCKAY plot method and the data observed. Comparing these k with each other has led to the following four conclusions in the T-for-H exchange reaction. (1) The reactivity of both the COOH and OH group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(7 reference statements)
0
7
0
Order By: Relevance
“…As for © mentioned above, it can be considered that the activity absorbed on the resin (i.e., HTO molecule absorbed on the resin) is smaller at a higher temperature. Previously [1,2], as for the T-forBrought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/29/15 2:08 AM Η exchange reaction, the higher the temperature is, the greater the activity is of the material used, while that for the OT-for-OH exchange reaction, the reverse result is seen. This appears to be due to decrease a rate of dissociation of HTO, leading to a lower amount of OT~ with an increasing temperature.…”
Section: Ot-for-oh Exchange Reaction (And T-for-h Exchange Reaction)mentioning
confidence: 55%
See 3 more Smart Citations
“…As for © mentioned above, it can be considered that the activity absorbed on the resin (i.e., HTO molecule absorbed on the resin) is smaller at a higher temperature. Previously [1,2], as for the T-forBrought to you by | New York University Bobst Library Technical Services Authenticated Download Date | 6/29/15 2:08 AM Η exchange reaction, the higher the temperature is, the greater the activity is of the material used, while that for the OT-for-OH exchange reaction, the reverse result is seen. This appears to be due to decrease a rate of dissociation of HTO, leading to a lower amount of OT~ with an increasing temperature.…”
Section: Ot-for-oh Exchange Reaction (And T-for-h Exchange Reaction)mentioning
confidence: 55%
“…2. From the figure, it is found that © the real activity of IRA-400 based on OT-for-OH exchange reaction decreases with increasing temperature within the range of 40 ~ 80° C, © the real activity of IR-120B based on T-for-H exchange reaction increases with increasing temperature within the range of 20 ~ 80° C. Examining the results mentioned above, the following three points can be considered: (a) the exchange capacity of each resin may vary with temperature; (b) the degree of the dissociation of HTO water may vary with temperature; (c) the ratio of the rate of the dissociation of Formula (2) with that of Formula (3) may vary with temperature. However, in general, the exchange capacities of ion exchange resins hardly decrease within the range of 20 ~ 80° C [8].…”
Section: Effect Of Temperature On the Reactivity Of Each Ion-exchangementioning
confidence: 97%
See 2 more Smart Citations
“…The reactivity of several materials [1] has been clarified using the rate constants (k) for the materials in the hydrogen-isotope exchange reaction. These k values were calculated using both the A"-McKay plot method [2,3] and the data obtained in the gas-solid [4,5] (or liquid-solid [6,7]) system.…”
Section: Introductionmentioning
confidence: 99%